Information Technology, Artificial Intelligence and Environmental Sustainability: An Analytical Review of the Arab and Libyan Contexts (Al-Farooq Journal of Sciences, 2026)
This paper examines the interlinked relationship between information technology and artificial intelligence on the one hand, and environmental sustainability on the other, drawing on an analysis of academic literature and international reports issued mainly between 2020 and 2026. It adopts a critical analytical review of recent literature, proceeding from a defined research problem and clear sub-questions, and highlights the environmental paradox of artificial intelligence: its capacity to help reduce environmental risks alongside its growing burdens in terms of energy and water consumption and electronic waste generation. The study discusses the contribution of these technologies to improving energy efficiency, supporting precision agriculture, managing smart cities and monitoring environmental change, set against the environmental costs that accompany them. It further sheds light on this relationship in the Arab region, and in Libya in particular, where the challenges of water scarcity, desertification and dependence on fossil fuels intersect with promising opportunities to adopt digital and intelligent solutions in the energy and water sectors. The paper concludes that the environmental impact of artificial intelligence is not determined automatically by the nature of the technology itself, but rather depends on how it is deployed and on the extent to which it is coupled with effective governance policies and efficiency-oriented design from the earliest stages. The paper offers a set of practical recommendations for decision-makers in Libya and the Arab region.
Keywords: Artificial Intelligence; Green Computing; Environmental Sustainability; Carbon Footprint; Water Footprint; Libya; Sustainable Development Goals.